Visual and Verbal Working Memory and Processing Speed Across the Adult Lifespan: The Effect of Age, Sex, Educational Level, Awakeness, and Hearing Sensitivity - Kestens, Katrien; Degeest, Sofie; Miatton, Marijke; Keppler, Hannah (Frontiers in Psychology, 2021)
Objective: To strengthen future methodological choices regarding the measurement of cognition within the field of audiology, the current study aimed to examine the effect of, among other things, hearing sensitivity on the backward corsi tapping task (i.e., visual working memory and processing speed) and the letter-number sequencing task (i.e., verbal working memory and processing speed). Design and Study Sample: The backward corsi tapping task and the letter-number sequencing task were administered to 184 participants, aged between 18 and 69 years. The effect of age, sex, educational level, awakeness, and hearing sensitivity on verbal and visual working memory and processing speed was assessed using stepwise multiple regression analyses. Results: For all outcome variables, a decrease in performance was observed with increasing age. For visual and verbal working memory, males outperformed females, whereas no clear sex effect was observed for visual and verbal processing speed. Hearing sensitivity had only a significant impact on visual processing speed. Conclusion: The importance to evaluate cognitive construct validity within audiological research was highlighted. Further research should focus on investigating the associations between speech understanding on the one hand and the backward corsi tapping task and letter-number sequencing task on the other hand.